An Examination of the First 30 Days After Patients are Discharged to the Community From Hip Fracture Postacute Care. Issue 10 (October 2015) - Leland, Natalie E.; Gozalo, Pedro; Christian, Thomas J.; Bynum, Julie; Mor, Vince; Wetle, Terrie F.; Teno, Joan M.
Abstract : Background: Postacute care (PAC) rehabilitation aims to maximize independence and facilitate a safe community transition. Yet little is known about PAC patients' success in staying home after discharge or differences on this outcome across PAC providers. Objectives: Examine the percentage of PAC patients who remain in the community at least 30 days after discharge (ie, successful community discharge) after hip fracture rehabilitation and describe differences among PAC facilities based on this outcome. Research Design: Retrospective observational study. Subjects: Community-dwelling, Medicare fee-for-service beneficiaries 75 years of age and above who experienced their first hip fracture between 1999 and 2007 (n=880, 779). PAC facilities admitting hip fracture patients in 2006. Measures: Successful community discharge, sites of readmission after PAC discharge. Results: Between 1999 and 2007, 57% of patients achieved successful community discharge. Black were less likely (adjusted odds ratios=0.84; 95% confidence interval, 0.82–0.86) than similar whites to achieve successful community discharge. Among all who reentered the community (n=581, 095), 14% remained in the community <30 days. Acute hospitals (67.5%) and institutional PAC (16.8%) were the most common sites of reentry. The median proportion of successful community discharge among facilities was 49% (interquartile range, 33%–66%). Lowest-quartile facilities admitted older (85.9 vs. 84.1 y of age), sicker patients (eg, higher rates of hospital complications 6.0% vs. 4.6%), but admitted fewer annually (7.1 vs. 19.3), compared with the highest quartile. Conclusions: Reentry into the health care system after PAC community discharge is common. Because of the distinct care needs of the PAC population there is a need for a quality measure that complements the current 30-day hospital readmission outcome and captures the objectives of PAC rehabilitation.